2015
DOI: 10.1002/asi.23370
|View full text |Cite
|
Sign up to set email alerts
|

Updating the SCImago journal and country rank classification: A new approach using Ward's clustering and alternative combination of citation measures

Abstract: This study introduces a new proposal to refine the classification of the SCImago Journal and Country Rank (SJR) platform by using clustering techniques and an alternative combination of citation measures from an initial 18,891 SJR journal network. Thus, a journaljournal matrix including simultaneously fractionalized values of direct citation, cocitation, and coupling was symmetrized by cosine similarity and later transformed into distances before performing clustering. The results provided a new cluster-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Obviously, the accuracy of a journal classification system can heavily influence the results of any study that analyses the level of interdisciplinarity/multidisciplinarity, productivity and research impact in the different scientific disciplines involved in a set of journals classified within the same field. For that reason, the precision of the WoS and Scopus journal classification systems has been a constant matter of concern among researchers, who have analysed several options to validate and improve them (Janssens et al 2009;López-Illescas et al 2009;Zhang et al 2010;Thijs et al 2015;Gómez-Núñez et al 2016;Urbano et al 2005). Despite these efforts, Leydesdorff and Bornmann (2015) explored the use of WoS categories for calculating field-normalized citation impact indicators in the areas of information science and science and technology studies and concluded that the use of this category might seriously harm the quality of the evaluation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Obviously, the accuracy of a journal classification system can heavily influence the results of any study that analyses the level of interdisciplinarity/multidisciplinarity, productivity and research impact in the different scientific disciplines involved in a set of journals classified within the same field. For that reason, the precision of the WoS and Scopus journal classification systems has been a constant matter of concern among researchers, who have analysed several options to validate and improve them (Janssens et al 2009;López-Illescas et al 2009;Zhang et al 2010;Thijs et al 2015;Gómez-Núñez et al 2016;Urbano et al 2005). Despite these efforts, Leydesdorff and Bornmann (2015) explored the use of WoS categories for calculating field-normalized citation impact indicators in the areas of information science and science and technology studies and concluded that the use of this category might seriously harm the quality of the evaluation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Alternative tests with other clustering algorithms like k-means, single linkage and complete linkage were executed in R statistical software, but the results were not satisfactory: most of the distributions were skewed, with a few crowded journal clusters and an abundance of small clusters and singletons. Only the Ward method, likewise used in a related study (Gómez-Núñez et al, 2016) gave us acceptable results despite the generation of a couple of superclusters of journals. Therefore, on the basis of previous tests and because of their integration in Pajek and VOSViewer software, the VOS method algorithm was selected and run on the normalized journal network integrating the three citation-based links.…”
Section: Vos Clustering Performancementioning
confidence: 95%
“…As a hierarchical agglomerate cluster algorithm, the WCM has a wide range of applications [1921]. First, it is started by accepting each node as a separate cluster.…”
Section: Classification Model Of Emitter Signalsmentioning
confidence: 99%